1999
DOI: 10.1046/j.1439-0523.1999.118002131.x
|View full text |Cite
|
Sign up to set email alerts
|

Different types of resistance against greenbug, Schizaphis graminum Rond, and the Russian wheat aphid, Diuraphis noxia Mordvilko, in wheat

Abstract: A collection of 26 cultivars of wheat Triticum aestivum were screened for resistance against the two main aphid pests of cereals, the greenbug Schizaphis graminum Rond. and the Russian wheat aphid (RWA) Diuraphis noxia Mordvilko. Since genetic variability has been found in Argentinean populations of both aphid species, this work was aimed at determining the response of different types of resistance in wheat cultivars when infested with aphids. Antixenosis, antibiosis and tolerance were evaluated with tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
1
10
0
6
Order By: Relevance
“…These were reared on a susceptible barley cultivar (ÔBordenave RanquelinaÕ) and a wheat cultivar (ÔBuck Ombu´Õ), under natural conditions at La Plata (36°36¢ S.L.). The clone used has been characterized as biotype C (Castro et al 1999). Russian wheat aphids (RWAs), Diuraphis noxia Mordvilko, were also collected on T. turgidum conv.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were reared on a susceptible barley cultivar (ÔBordenave RanquelinaÕ) and a wheat cultivar (ÔBuck Ombu´Õ), under natural conditions at La Plata (36°36¢ S.L.). The clone used has been characterized as biotype C (Castro et al 1999). Russian wheat aphids (RWAs), Diuraphis noxia Mordvilko, were also collected on T. turgidum conv.…”
Section: Methodsmentioning
confidence: 99%
“…Greenbug and the Russian wheat aphid (RWA) are two serious insect pests of wheat, causing heavy losses in many countries (Hill et al 1993, Dong et al 1997. Although these aphids can be controlled by the application of pesticides, the breeding of genetic resistance can, and has been, used extensively (Castro et al 1999). Six genes for resistance have been introduced into wheat to control greenbug, and another nine to control RWA (Worland and Snape 2001).…”
mentioning
confidence: 99%
“…However, antixenosis, or non-preference, could comprise an additional component of resistance that has not yet been exploited, even though it has been identified in a number of wheat cultivars. For example, Castro et al (1999) found that eight out of 26 tested wheat cultivars showed antixenosis. Similarly Miller et al (2003), observed antixenosis to D. noxia in PI 222668 and PI 372129.…”
Section: Introductionmentioning
confidence: 99%
“…This species was first found in Chile in 1988 and in Argentina in 1992 (Ortego & Delfino, 1994). It was found in the main cereal producing region of Argentina, south of Buenos Aires province, in 1994(Bellone & Almaraz, 1995, and then spread northwards and eastwards infesting barley and wheat (Triticum aestivum and T. durum) in 1995 (Castro et al, , 2001. Parasitoids and chemicals failed to control this pest, possibly because it causes the leaves to curl tightly, which protects the enclosed aphids (Burd et al,1998).…”
Section: Introductionmentioning
confidence: 99%